ARCHAEOLOGICAL GEOPHYSICS IN THE WORLD AND IN UKRAINE: BEGINNING, DEVELOPMENT, PRESENT - Bondar, K.; Vyzhva, S.; Sheiko, I.; Kozlenko, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article describes the history of the development of geophysical methods in archaeological studies in Europe, the USA, the former USSR and Ukraine. In the 1950s the researchers quickly proceeded from the first sampling to the mass magnetic and electric measurements. In the 1980s there was a transition to digital registration during field studies, as well as rapid development of data processing. This led to the introduction of some geophysical methods in archaeology, which require complex calculations when processing the signal and inversion of data, such as georadar method, electrical resistivity tomography, induction method, etc. At the current stage, there is a need to interpret these more and more detailed and largescale geophysical data in the context of the differentiation of more and more weak in contrast physical properties, and small-scale inhomogeneities in the soil cover. Confirmation of the anthropogenic and technogenic occurrence of geophysical anomalies is searched for using direct measurement and modeling of physical parameters of soil and archaeological materials. The work also presents the achievements of domestic geophysicists, as they became the basis for the great modern archeological projects and made the archeological geophysics the fundamental part of the cultural heritage research in Ukraine.
Keywords: geophysical methods, archeological site, review, Ukraine, magnetometry, electrical resistivity tomography, ground penetrating radar